Sifat Fisis Dan Mekanis Baja Karbon Rendah Dengan Perlakuan Carburizing Arang Bambu - Karim, Muhammad rizqi; , Supriyono, ST, MT, Ph.D (2017)
Pack carburizing carburizing is the simplest method, which uses charcoal powder as the addition of the element carbon. The purpose of this study was to determine changes in the properties of steel, good physical properties and mechanical properties after a pack carburizing process with carbon materials bamboo charcoal. Material selection is done by testing the soft steel (mild steel) <0.3% C, as a raw material by means of Optical Emission Spectrometer. Specimen together with a mixture of bamboo charcoal and NaCO3 inclusion in pottery, kitchen and heated in a heater (furnace) at a temperature of 980ºC with a brace for 2 hours. Specimen results carburizing pack tested micro Vickers hardness method using a Micro Hardness Tester, a total of 9 points. To use the tool microstructure bservation Inverted Metallurgical MicroscopeResults of testing the chemical composition of the most widely element after iron (Fe = 98.83%) is manganese (Mn = 0.264%), manganese (Mn) is less than 8.0%, so that the raw material is included in the low alloy steel. The observation of micro structure more raw material than crystal crystal ferrite pearlite. While icrostructure pack carburizing 2 hours using bamboo charcoal media more than ferrite pearlite crystals. This shows that the steel workpiece to increase the hardness after a arburizing process. Results of hardness testing on raw materials has a Vickers hardness value of an average of 183.817 VHN. While the average hardness of objects after a carburizing process with bamboo charcoal media amounted to 219.085 VHN. So workpieces after carburizing increased violence by 19.18%